Violence Against Prostitutes and Non-prostitutes: An Analysis of Frequency, Variety and Severity. Issue 15 (August 2022) - Zara, Georgia; Theobald, Delphine; Veggi, Sara; Freilone, Franco; Biondi, Eleonora; Mattutino, Grazia; Gino, Sarah
Violence against women is a form of gender violence, and the lethal aspect of it, defined as femicide, is a global health and human rights problem. This study looked at 330 cases of femicide that occurred in North West Italy, between 1970 and 2020, committed by 303 male perpetrators. The victims included women who were prostitutes and those who were not. Findings show that only a small proportion of femicide occurs within an anonymous setting: Victims were mostly killed by a man they knew. The type and intensity of the relationship was likely to affect how the violence occurred. In those cases in which victims and perpetrators had an intimate relationship, the risk of overkill, that is, an excessive use of violence that goes further than what is necessary to cause death, was four times higher in comparison with the murder of unknown victims. As with non-prostitutes, the risk of overkill was almost fourfold for those prostitutes who knew their perpetrators. Furthermore, when comparing prostitutes with any unknown victims, the risk of being overkilled was almost five times higher for the former, suggesting that prostitutes are more at risk of being murdered with excessive violence. In addition, prostitutes were more likely to be victims of sexual murder, postmortem mutilation, and being killed by men who had previous criminal records. Women who are victims of violence are not a homogeneous group, although some of the psychosocial correlates are the same and relevance should be given to the features behind the type, intensity, and nature of the relationship between prostitutes and non-prostitutes and their perpetrators. These variables are what make violence against women a preventable problem.